2017
DOI: 10.3389/fnmol.2017.00199
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Features of Doublecortin as a Marker of Neuronal Migration and Its Implications in Cancer Cell Mobility

Abstract: Neuronal migration is a critical process in the development of the nervous system. Defects in the migration of the neurons are associated with diseases like lissencephaly, subcortical band heterotopia (SBH), and pachygyria. Doublecortin (DCX) is an essential factor in neurogenesis and mutations in this protein impairs neuronal migration leading to several pathological conditions. Although, DCX is capable of modulating and stabilizing microtubules (MTs) to ensure effective migration, the mechanisms involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 126 publications
7
81
0
1
Order By: Relevance
“…DCX, an essential factor in the differentiation and migration of newborn neurons, is used as a marker to detect the process of neural recruitment. In this study, immunofluorescence experiments confirmed that silencing α-Syn mainly upregulates muscarinic or nicotinic cholinergic receptors to promote DCX production, promote nerve regeneration at the injury site as well as improve motor function [28]. In summary, the mechanisms of Chrm2 and Chrm2 in this study complement each other.…”
Section: Nicotinic Cholinergic Receptor (Nachr)supporting
confidence: 72%
“…DCX, an essential factor in the differentiation and migration of newborn neurons, is used as a marker to detect the process of neural recruitment. In this study, immunofluorescence experiments confirmed that silencing α-Syn mainly upregulates muscarinic or nicotinic cholinergic receptors to promote DCX production, promote nerve regeneration at the injury site as well as improve motor function [28]. In summary, the mechanisms of Chrm2 and Chrm2 in this study complement each other.…”
Section: Nicotinic Cholinergic Receptor (Nachr)supporting
confidence: 72%
“…see above nestin see above immature neurons DCX protein that facilitates microtubule polymerization, a marker of migrating neuroblasts and immature neurons [30] ÎČIII tubulin microtubule protein, expressed in immature neurons and differentiated neurons [31] neurons MAP2 protein involved in the growth and assembly of microtubules, required for neurite formation in neurons [32] astrocytes GFAP see above S100ÎČ…”
Section: Sox1mentioning
confidence: 99%
“…Next, we analysed the levels of doublecortin (DCX), a marker of immature neurons [41]. DCX is a microtubule-associated protein, which is necessary in the proliferation of progenitor cells during neurogenesis [42,43]. Optical density of DCX immunofluorescence images within the peri-infarct region were quantitatively assessed using a threshold analysis protocol.…”
Section: Gh Treatment Promotes Cell Proliferation and Neurogenesis Wimentioning
confidence: 99%